Digital Future: Intellectual Property Issues in Industry 4.0. - A. S. Kharlanov (Informaciâ i Innovacii, 2022)
Digital future is coming by the way on the basis of executive questions forming in front of the mankind as quality control of labor resources in case of specialization determination and acceptance of potential equity of unique functions, which are useful for human beings but not for AI systems applications. The questions of intellectual property in the providing 7-th scientifically and technological structure are performing the business opportunities of society development to the first place of information domination in various areas starting from banking sources of ecosystems creation by the digital services of infrastructures chargers and transformers of operational basis, to marketplaces, calculation and payment systems, concentrated diversification of multifunctional economical actors of market area, which are giving free and easy access to the people to creature comforts. This is an IoT and unique products issuing by the 3-D printers using, communication systems development and data base transferring on the ICT supporting providers and vendors.